Analysis of students CRI (Certainty of Response Index) of genetic concept based two-tier diagnostic test online using I spring suite 8 for covid-19 learning - Ismi Nurul Qomariyah; Mistianah Mistianah (Universitas Muhammadiyah Surabaya, 2020)
Abstract. Technology-based learning in the covid-19 pandemic period faced manyobstacles and challenges. Consequently, the learning design and strategy are expected to be effective, efficient and able to empower student competencies appropriately. One of the important points in learning during the Covid-19 epidemic was an effective learning evaluation. One of the effective learning evaluation in pandemic period is the online multiple-choice test. However, multiple-choice tests in the form of online quizzes also have some short ages, for example, it is quite difficult to capture the student‘s mastery concepts evel in more depth and detail. Therefore an online multiple choice test evaluation form can be developed with a two-tier system, so that it can showed the level of students understanding and thinking further. Moreover, the certainty of response index also added to determine the level of student confidence in the answers given. The purpose of this study was to analyze the student‘s understanding with the Certainty of Response Index (CRI) on genetic material using two-tier online diagnostic test based on the I spring suite 8application. The method used is descriptive. The subjects were all 2018A IKIP Budi Utomo Malang students, with the total number of 18 students. The results showed that the CRI level of students tends to be low, the answers and reasons are not correct and related each other, so it seems that the students are answer randomly which unable to show logical reasons related to answers. Some factors that causing the low level of student understanding and CRI are the characteristics of genetic material that‘s abstract and difficult, the scope of the material are complex and complicated, the initial ability of students, and the use of learning resources that are not optimal.